Cost estimation and willingness to pay for Hepatitis B vaccination in Selangor, Malaysia - Rajamoorthy, Yogambigai (2017)
The World Health Organization estimated that 240 million humans worldwide were chronically infected by Hepatitis B virus. In Malaysia, one million nationals are estimated to be infected and the projected incidence rate shows an increasing pattern. Moreover, Malaysian household risk behaviour is unknown. HB vaccination for infant was compulsory since 1989; however, those born before 1989 need to spend their own money to be vaccinated in private clinic/hospitals. However, Malaysian health system is moving towards enhancing efficiency, effectiveness, and collaboration with private sectors and non-governmental organisations as well as promoting health tourism. Therefore, standard market price will be required for the HB vaccination, based on the national affordability. This study aims to determine the association between perceptions to Hepatitis B vaccination on respondent’s willingness to pay (WTP), to identify the risk behaviors and the determinants of socio-demographic factors on Hepatitis B behavior and to determine the determinants of willingness to pay for Hepatitis b vaccination. Stratified two stage cluster sampling of 768 respondents with face to face interview were conducted in housing areas in Selangor. Respondents aged above 20 were included in this study. The responses rate of 94% achieved. Partial Least Square-Structural Equation Model (PLS-SEM) was used to test the association between WTP and perception variable using the Health Belief Model (HBM). Multivariate analysis was then conducted to test the relationship between socioeconomics variables with risk behaviour of HB infection. Finally, the Contingent Valuation Method (CVM) to were used to estimate Selangor’s residents’ economic value for the self-paid HB vaccination which determined the WTP mean among the respondents by considering respondents’ perceptions of HB and HB vaccination. The PLS-SEM results showed a positive relationship between perceived susceptibility, perceived barriers, and cues to action with WTP. Perceived barriers had significant influence on perceived benefit of HB vaccination. Multivariate analysis showed that males are more exposed to the risk behaviour of sharing of needles, razor blades,toothbrushes, getting tattoos, having unhealthy sex behaviours, and abusing alcohol. The result from CVM showed that respondents were WTP RM337.826 for three doses. Bid value, education, income, race, and perceived susceptibility were the determinants of willingness to pay for Hepatitis B vaccination. The estimated aggregate welfare gains amounts to RM367, 179,025.49. This amount indicates that government is able to allocate this sum amount of money for other expenses, if the majority of the nation is WTP for self-paid HB vaccination. The findings contribute to implementation of policy with little or no cost to private and public healthcare providers. We suggest that enforcement of policies to the nation by Health Ministry such as increase awareness trough social communication including Facebook, webpages, Instagram, television and radio announcements, poster design in various languages, flexi vaccination services, as well as monitoring and regulating the vaccination price in private clinics. The nation should be encouraging to undergo HB screening programme and taking HB vaccine if required at subsidised or discounted priced which may be contributed also by the private health care providers (private sectors).